Pten controls B‐cell responsiveness and germinal center reaction by regulating the expression of IgD BCR. (23rd April 2019) - Setz, Corinna S; Khadour, Ahmad; Renna, Valerio; Iype, Joseena; Gentner, Eva; He, Xiaocui; Datta, Moumita; Young, Marc; Nitschke, Lars; Wienands, Jürgen; Maity, Palash C; Reth, Michael; et al.
Abstract: In contrast to other B‐cell antigen receptor (BCR) classes, the function of IgD BCR on mature B cells remains largely elusive as mature B cells co‐express IgM, which is sufficient for development, survival, and activation of B cells. Here, we show that IgD expression is regulated by the forkhead box transcription factor FoxO1, thereby shifting the responsiveness of mature B cells towards recognition of multivalent antigen. FoxO1 is repressed by phosphoinositide 3‐kinase (PI3K) signaling and requires the lipid phosphatase Pten for its activation. Consequently, Pten‐deficient B cells expressing knock‐ins for BCR heavy and light chain genes are unable to upregulate IgD. Furthermore, in the presence of autoantigen, Pten‐deficient B cells cannot eliminate the autoreactive BCR specificity by secondary light chain gene recombination. Instead, Pten‐deficient B cells downregulate BCR expression and become unresponsive to further BCR‐mediated stimulation. Notably, we observed a delayed germinal center (GC) reaction by IgD‐deficient B cells after immunization with trinitrophenyl‐ovalbumin (TNP‐Ova), a commonly used antigen for T‐cell‐dependent antibody responses. Together, our data suggest that the activation of IgD expression by Pten/FoxO1 results in mature B cells that are selectively responsive to multivalent antigen and are capable of initiating rapid GC reactions and T‐cell‐dependent antibody responses. Synopsis: By activation of Ig gene rearrangement and receptor editing, Pten controls antibody diversity and the development of self‐tolerant B cells. Pten also controls the development of follicular B cellsand their responsiveness towards complex antigen. Pten is required for receptor editing but not for anergy in B cells. Increased IgD BCR expression results in mature B cells that are controlled by soluble antigen whileresponsive to antigencomplexes. Pten activates IgD BCR expression and selective B cell responsiveness through FoxO1. IgD regulates the quality of immune responses by efficiently directing B cells into GC reactions. Abstract : Regulation of PI3‐kinase‐FoxO1 by the lipid phosphatase PTEN is critical for the activation of IgD expression, which is needed for the generation of mature B cells fully responsive to antigen complexes.